Clusterin suppresses invasion and metastasis of testicular seminoma by upregulating COL15a1 - Yankang Cui (Elsevier, 2021)
Seminoma is the most common subtype of testicular germ cell tumor, with an increasing incidence worldwide. Clusterin (CLU) expression was found to be downregulated in testicular seminoma in our previous study. We now expanded the sample size, and further indicated that CLU expression correlates with tumor stage. Tcam-2 cell line was used to investigate the CLU function in testicular seminoma, and CLU was found to inhibit the proliferation and metastasis abilities. Besides, extracellular matrix protein COL15a1 was demonstrated as the downstream of CLU to affect the epithelial-mesenchymal transition (EMT) process via competitively binding to DDR1 with COL1A1 and inhibiting the phosphorylation of PYK2. MEF2A was found to interact with CLU and bind to the promoter of COL15a1 and so upregulate its expression. This is the first study using testicular xenografts in situ to simulate testicular seminoma metastatic and proliferative capacities. In conclusion, CLU acts as a tumor suppressor to inhibit the metastasis of testicular seminoma by interacting with MEF2A to upregulate COL15a1 and blocking the EMT process.